Development of near-infrared xanthene fluorescence probe for the highly selective and sensitive detection of cysteine. (November 2019) - Wu, Yongquan; Shi, Aiping; Zeng, Hong; Li, Yuanyan; Li, Huifang; Chen, Xiaoyong; Wong, Wai-Yeung; Fan, Xiaolin
Abstract: Abnormal levels of the biological thiol cysteine (Cys) have been shown to be associated with growth retardation, skin lesions, and neurotoxicity in humans. In order to fully elucidate the role of Cys in biological systems, its levels must be monitored through in vitro assays as well as in living cells and animals. Herein, we designed and synthesized a novel near-infrared xanthene fluorescence probe (NOF1) with an acrylate group as a trigger moiety to detect Cys over homocysteine and glutathione. The NOF1 probe exhibited a good selectivity and a high sensitivity toward Cys, with a detection limit of 210 nM. Additionally, NOF1 retained good sensitivity and selectivity in human plasma, with a good recovery of Cys within the range 98%–102%. Importantly, the NOF1 probe was successfully applied to the fluorescence imaging of Cys in living cells, zebrafish, and mice, showing great potential for applications involving the detection of Cys both in vitro and in vivo . Graphical abstract: A novel NIR xanthene fluorescence probe showed sensitive and selective response toward Cys, and was developed to detect endogenous Cys in vivo .Image 1 Highlights: A simple strategy to synthesize a novel near-infrared xanthene fluorescence sensor for Cys detection. Powerful selectivity and sensitivity for Cys was achieved to differentiate similar bio-thiols (Hcy and GSH). Practical applicability of our sensor for accurately quantifying Cys levels in the human plasma with a good recovery rate. The sensor as a versatile probe was introduced to detect or image Cys in living cells, zebrafish, and mice. A novel NIR xanthene fluorescence probe showed sensitive and selective response toward endogenous Cys in vivo.